Role of menopausal hormone therapy in the prevention of postmenopausal osteoporosis - Na Zhao; Wei Wei; Xu Yingfang; Li Dong; Yin Beili; Gu Weiqun (Open Life Sciences, 2023)
The use of menopausal hormone therapy (MHT) has declined due to concerns about its potential side effects. However, its pivotal role in managing postmenopausal osteoporosis is gaining increased recognition. In this article, we explore how MHT assists postmenopausal women in maintaining bone health and preventing fractures. Recent research indicates that MHT significantly reduces the risk of fractures in women. This benefit is evident regardless of a woman’s bone mineral density or their use of progestogens. However, there is limited evidence suggesting that the skeletal benefits continue once the treatment is discontinued. Possible complications of MHT include heart attacks, clots, strokes, dementia, and breast cancer. The most suitable candidates for MHT are women who have recently entered menopause, are experiencing menopausal symptoms, and are below 60 years of age with a minimal baseline risk of adverse events. The treatment is available to those who meet these criteria. For women undergoing premature menopause, MHT can be considered as a means to protect bone health, especially if initiated before menopause or if accelerated bone loss is documented soon after menopause. Such decisions should be made after evaluating individual risk factors and benefits.